Giant zero-biased flexible magnetoelectric laminate composites for wearable magnetic sensor. (November 2018) - He, Xingduo; Qiu, Jing; Long, Yibing; Chang, Qijie; Hu, Zhenwen; Liu, Huanbin; Hu, Wei; She, Yin; Tang, Xiaosheng
Abstract: Flexible magnetoelectric (ME) laminate composites consist of polyvinylidene fluoride (PVDF) and nanocrystalline alloy (FeCuNbSiB) were prepared. The ME coupling properties under different bending angle ( θ ) at zero dc bias magnetic field ( H dc ) were investigated. The experimental results demonstrate the optimum zero-biased resonant ME voltage coefficient (MEVC) of ME laminate composites can reach 17.65 V/(cm·Oe). This is mainly due to the large permeability and low saturation magnetostrictive coefficient of the nanocrystalline alloy. The induced zero-biased ME voltages of ME laminate composites show an excellent linear relationship to ac magnetic field at bending states over a wide range. This laminate composite shows promising applications for high-sensitivity and small-size wearable magnetic sensors without bias.